2022
DOI: 10.1039/d2cp00906d
|View full text |Cite
|
Sign up to set email alerts
|

Revealing intrinsic spin coupling in transition metal-doped graphene

Abstract: Graphene materials offer attractive possibilities in spintronics due to the unique atomic and electronic structures, which contrasts with their limited applications in the design of sophisticated spintronic devices. This should...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 94 publications
0
8
0
Order By: Relevance
“…The planewave cutoff energy of 500 eV is used, and the energies and residual forces are converged to 10 –5 eV and 0.01 eV/Å for electronic and geometric optimizations, respectively. In this work, we only consider the ground spin state for all atomic and electronic structure calculations; further considering more spin states in the future will give a more comprehensive picture of the catalytic properties of the materials. , Through testing, it is found that the influence of different k -point samplings on the adsorption Gibbs free energy is insignificant (usually less than 0.1 eV). Besides, since the lattice parameters a and b have exceeded 20 Å, too dense k -points will greatly increase the computational cost.…”
Section: Methodsmentioning
confidence: 99%
“…The planewave cutoff energy of 500 eV is used, and the energies and residual forces are converged to 10 –5 eV and 0.01 eV/Å for electronic and geometric optimizations, respectively. In this work, we only consider the ground spin state for all atomic and electronic structure calculations; further considering more spin states in the future will give a more comprehensive picture of the catalytic properties of the materials. , Through testing, it is found that the influence of different k -point samplings on the adsorption Gibbs free energy is insignificant (usually less than 0.1 eV). Besides, since the lattice parameters a and b have exceeded 20 Å, too dense k -points will greatly increase the computational cost.…”
Section: Methodsmentioning
confidence: 99%
“…These gates can be realized based on different spin-dependent current-voltage characteristics [ 42 ]. The work by the Han Zhou group thoroughly examines the spin couplings between transition metal atoms doped on graphene and demonstrates how they may be used to create various logic gates for spintronic device design [ 43 ]. The spin-coupling effect can manifest a certain distance dependence and space propagation, as further confirmed by the impacts of the number of carbon layers and the distance between doped metal atoms on the logic gate implementation.…”
Section: Applicationsmentioning
confidence: 99%
“…More importantly, 2D materials possess a high specific surface area with the ultimate exposure of atoms, which can provide a large number of sites for surface modification to regulate intrinsic properties. Surface modification with chemical species (atom, ions, molecules) can induce charge doping, spin coupling, and lattice strain in 2D materials, tailoring their electronic structures and magnetic interactions, whereby new properties and functionalities are created [ 7 , 8 , 9 , 10 , 11 , 12 ]. The introduction of surface modification methods has resulted in the research on 2D materials flourishing further, which has caused vigourous development in the past decade.…”
Section: Introductionmentioning
confidence: 99%